L’accoglienza emergenziale. Pratiche di resistenza dei richiedenti asilo e il ruolo dell’antropologo - Guida, Cecilia (Antropologia Pubblica, 2017)
This paper stems from a fieldwork I carried on for a period of ten months in a CAS (Centre for extraordinary hospitality) for asylum seekers where I played a double role, both as reception operator and as researcher. Through some ethnographic descriptions my purpose is twofold: on one hand I mean to analyze how the emergency paradigm leads to control and compassion politics, both aimed at a securitarian management of asylum seekers; on the other my work highlights how the awareness achievement process of asylum seekers' rights turned them into active players, thus deconstructing the image of passive victims. Finally, by examining my position in the Nicara Center, I would like to suggest some considerations upon the role of the anthropologist, who is to be considered not only in the field of ethnographic analysis, but also as an active player in everyday emergencies thanks to his reflective and critical qualities on anthropological knowledge, which are essential in order to promote a different kind of reception by acting as direct witness and no longer as simple observer. Based on this premises, my main objective is that of analyzing how the anthropological knowledge can be intended not only towards observation aimed at understanding security and power balances, but also towards a change in the context by promoting a kind of anthropology ready to implement social interventions which deconstruct emergency logics and, at the same time, capable of preserving its theoretical depth and self-reflective dimension.